Techniques for Non-Invasive Monitoring of Arterial Blood Pressure - Meidert, Agnes S.; Saugel, Bernd (Frontiers in Medicine, 2018)
Since both, hypotension and hypertension, can potentially impair the function of vital organs like heart, brain, or kidneys, monitoring of arterial blood pressure is a mainstay of hemodynamic monitoring in acutely or critically ill patients. Arterial blood pressure can either be obtained invasively via an arterial catheter or noninvasively. Noninvasive blood pressure measurement provides either intermittent or continuous readings. Most commonly, an occluding upper arm cuff is used for intermittent noninvasive monitoring. Blood pressure values are then obtained either manually (by auscultation of Korotkoff sounds or palpation) or automatically (by oscillometry). For continuous noninvasive blood pressure monitoring, the volume clamp method or arterial applanation tonometry can be used. Both techniques enable the arterial waveform and blood pressure values to be obtained continuously. This article describes the different techniques for noninvasive blood pressure measurement, their advantages and limitations, and their clinical applicability.